Behind the scenes soccer - Greder, Andy 1983 (Inside the sport (Lerner sports), 2020)
"Soccer captures the attention of fans around the world--but what are the lives of professional soccer players like behind the scenes? Discover how players prepare for games and learn about the other responsibilities they have when they aren't on the pitch"